2020
DOI: 10.1126/sciimmunol.abc2691
|View full text |Cite
|
Sign up to set email alerts
|

Defects in LC3B2 and ATG4A underlie HSV2 meningitis and reveal a critical role for autophagy in antiviral defense in humans

Abstract: Recurrent herpesvirus infections can manifest in different forms of disease, including cold sores, genital herpes, and encephalitis. There is an incomplete understanding of the genetic and immunological factors conferring susceptibility to recurrent herpes simplex virus 2 (HSV2) infection in the central nervous system (CNS). Here, we describe two adult patients with recurrent HSV2 lymphocytic Mollaret’s meningitis that each carry a rare monoallelic variant in the autophagy proteins ATG4A or LC3B2. HSV2-activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 75 publications
0
31
0
Order By: Relevance
“…Notably, it was shown that activity of the innate immune system protects against neurological complications [176]. It was recently reported that herpes-simplex-virus-2 (HSV-2) patients with defects in the autophagy genes ATG4A and LC3B2 develop recurrent meningitis (Mollaret's meningitis), a recurrent or chronic form of inflammation of the protective membranes covering the CNS [177,178]. Mechanistically, autophagy mediates the clearance of HSV-2 antigen in non-defective cells.…”
Section: Innate Immune Responses In Post-acute Conditions Of Persistent Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, it was shown that activity of the innate immune system protects against neurological complications [176]. It was recently reported that herpes-simplex-virus-2 (HSV-2) patients with defects in the autophagy genes ATG4A and LC3B2 develop recurrent meningitis (Mollaret's meningitis), a recurrent or chronic form of inflammation of the protective membranes covering the CNS [177,178]. Mechanistically, autophagy mediates the clearance of HSV-2 antigen in non-defective cells.…”
Section: Innate Immune Responses In Post-acute Conditions Of Persistent Virusesmentioning
confidence: 99%
“…Mechanistically, autophagy mediates the clearance of HSV-2 antigen in non-defective cells. Genetic disruption of ATG4A and LC3B2 expression led to enhanced viral replication and subsequent cell death in patient cells and cell lines [177].…”
Section: Innate Immune Responses In Post-acute Conditions Of Persistent Virusesmentioning
confidence: 99%
“…Mollaret's meningitis, the molecular and immunological pathogenesis of which is largely unexplored, is such a condition, and consists of recurrent lymphocytic meningitis caused by HSV-2 reactivation, in rare cases by VZV or HSV-1 [121][122][123]. Whole exome sequencing of patients with Mollaret's meningitis recently led to the identification of rare mono-allelic missense variants in the autophagy genes ATG4A and LC3B2 in two adult patients and was the first study to associate defective autophagy with viral infection in humans [124,125]. HSV-2 infection of fibroblasts from these patients demonstrated impaired virus-induced autophagy as well as increased viral replication and enhanced cell death, and this cellular phenotype was reconstituted/rescued to normal by expression of WT ATG4 and LC3B2 in the two patients, respectively [125].…”
Section: Role Of Autophagy In Reactivation Of Other Alphaherpesviruses the Example Of Mollaret's Recurrent Lymphocytic Meningitismentioning
confidence: 99%
“…Whole exome sequencing of patients with Mollaret's meningitis recently led to the identification of rare mono-allelic missense variants in the autophagy genes ATG4A and LC3B2 in two adult patients and was the first study to associate defective autophagy with viral infection in humans [124,125]. HSV-2 infection of fibroblasts from these patients demonstrated impaired virus-induced autophagy as well as increased viral replication and enhanced cell death, and this cellular phenotype was reconstituted/rescued to normal by expression of WT ATG4 and LC3B2 in the two patients, respectively [125]. These findings revealed a role for autophagy in antiviral defense and suggest that defective autophagy represents a rare inborn error of immunity associated with susceptibility to HSV2 CNS infection in humans.…”
Section: Role Of Autophagy In Reactivation Of Other Alphaherpesviruses the Example Of Mollaret's Recurrent Lymphocytic Meningitismentioning
confidence: 99%
“…Recently, studies on patients with HSV-2-induced recurrent lymphocytic Mollaret meningitis have begun to shed more light on a potentially important role of autophagy in viral infections and disease pathogenesis in humans. Whole-exome sequencing has revealed mutations in the autophagy genes LC3B2 and ATG4A in such patients, which were associated with impaired HSV-2-induced autophagy, increased viral replication and enhanced cell death in patient fibroblasts and in neuronal cells harboring the autophagy variants [71]. Based on these findings, it was suggested that autophagy may play an important role in antiviral defense in the CNS and that autophagy defects may represent an inborn error of immunity predisposing patients to viral meningitis and encephalitis [71].…”
Section: Conclusion and Overall Perspectivesmentioning
confidence: 99%